2017
DOI: 10.1039/c6py02161a
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally diketopyrrolopyrrole-functionalized dendritic oligothiophenes – synthesis, molecular structure, properties and applications

Abstract: Structure defined DPP functionalized conjugated thiophene dendrimers with a narrow optical band gap and a high TPA cross section are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…The investigated systems fall into a new family of dendritic oligothiophenes functionalized with DPP groups (DOT−p-DPPs) synthesized by Ma et al 13 (Chart 1). These macromolecules present oligothiophene units as the core electron donor and DPP groups as electron acceptors on the multibranched portion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigated systems fall into a new family of dendritic oligothiophenes functionalized with DPP groups (DOT−p-DPPs) synthesized by Ma et al 13 (Chart 1). These macromolecules present oligothiophene units as the core electron donor and DPP groups as electron acceptors on the multibranched portion.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, conjugated dendrimers are expected to have both advantages of good processability of polymers and good reproducibility of small molecules. 13 Inspired by these promising characteristics of this class of macromolecules, a new family of oligothiophene dendrimers decorated with diketopyrrolopyrrole (DPP) groups was investigated. In regard to their optical properties, there have been reports illustrating that some organic dendrimers show enhanced electronic coupling and very fast energy transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated dendrimers tend to have significantly larger 2PA cross‐section values in comparison to linear dendrimers, as a result of the higher density of chromophores in the ordered and confined geometry, strong interactions between chromophores, and highly efficient ICT . A family of 3D π‐conjugated DOT 89–93 that are functionalized with diketopyrrolopyrrole peripheral groups (DOT‐p‐DPPs) displayed the UV–vis absorption and fluorescence spectra which are shown in Figure . The spectra of compounds exhibiting comparable absorption properties can be divided into two regions: a high‐energy absorption band from 300 to 500 nm and a low‐energy absorption band occurring from 500 to 750 nm.…”
Section: Two‐photon Absorption Dendrimersmentioning
confidence: 99%
“…Due to their generally D–π–A–π–D character and thus resulting centrosymmetric arrangement, the DPP derivatives were most frequently studied as third-order optical NLOphores, in particular as two-photon absorbers (2PA). In this respect, the central DPP bicyclic lactam is often decorated with electron donors such as alkoxy- or dialkylamino groups [ 11 12 ], triphenylamine [ 13 14 ], heterocyclic carbazole [ 15 ], thiophene [ 16 – 17 ], furan [ 18 ], and organometallic ferrocene [ 19 ]. 2PA-active DPPs were utilized in two-photon excited fluorescence microscopy and bioimaging [ 13 14 ], most often upon their further structural tuning towards higher polar character and solubility in water [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some DPP derivatives also showed aggregation induced emission (AIE) [ 13 14 ] and the ability to selectively sense fluoride ions [ 26 – 28 ]. The modern era of DPP chromophores has been opened by Gryko et al [ 3 , 11 12 18 , 20 21 29 ] who have demonstrated their large and tunable two-photon absorption cross-section (δ 2PA ) generally ranging from 100–2500 GM, but for instance DPPs end-capped with imidazolium [ 21 ] or dendritic thiophenes [ 16 ] showed δ 2PA of 4000 and 7000 GM, respectively. However, to the best of our knowledge, the third-harmonic generation (THG) NLO process has not been investigated for DPP derivatives.…”
Section: Introductionmentioning
confidence: 99%